A political prayer: Praying the Lord’s Prayer in Caesar’s empire - Wright, Arthur M. (Review and expositor, 2021)
For many Christians around the world, the Lord’s Prayer is the most common prayer they pray, often on a daily or weekly basis. The temptation is to hear the word “prayer” and think strictly about spiritual matters. When this prayer of Jesus is read and interpreted in its Roman imperial context, however, it takes on new layers of meaning that are profoundly political. It has a significant bearing on how people of faith live under the dominion of empire while seeking to fully realize an alternative vision of God’s kingdom and justice on earth.